PERAMAH: Religious Moderation Educator Model for Early Childhood Based on Mark 10:13-16 - Kurniawan, Dody; Sasmita, Nisan; Nurwindayani, Efi (Didache: Journal of Christian Education, 2025)
Indonesia is a country rich in ethnic, cultural, and religious diversity. One of its key challenges is fostering harmony among people of different faiths. In this context, religious moderation education for early childhood becomes critically important to prevent radicalization and to nurture a spirit of tolerance. This research aims to explore how the example of Jesus in Mark 10:13–16 can serve as a model for religious moderation educators in early childhood. The study uses biblical exegesis to interpret the meaning of the scripture, as well as interviews and literature reviews to gather information from various relevant sources. The discussion reveals that the values of love, acceptance, and appreciation of differences as taught by Jesus can be effectively applied in early childhood education. This research successfully identifies the model of a Religious Moderation Educator for Early Childhood based on Mark 10:13–16, known as PERAMAH - Penerimaan (Acceptance), Empati (Empathy), Ramah (Friendliness), Apresiasi (Appreciation), Mendengarkan (Listening), Akomodasi (Accommodation), and Harmonisasi (Harmonization). It is recommended that early childhood educators implement religious moderation education using the PERAMAH model to build a more harmonious Indonesia today and in the future.